UPAYA MENINGKATKAN MINAT BACA MAHASISWA SEKOLAH TINGGI ILMU KESEHATAN BULELENG MELALUI APLIKASI KUBUK - Kadek Adi Swastawan (ACARYA PUSTAKA, 2025)
bstract The objectives of this research are: (1) To understand the reasons why the Library of the Buleleng School of Health Sciences (STIKES) prefers the Kubuku Application for library digitization, (2) To identify the challenges faced by the Library of the Buleleng School of Health Sciences (STIKES) in implementing the Kubuku Application, (3) To determine the impact of the Kubuku Application on the reading interest of students at the Buleleng School of Health Sciences (STIKES). This research uses a qualitative descriptive research method and informant determination techniques using purposive sampling and snowball sampling. The author chose the research location at the Buleleng School of Health Sciences (STIKES). In this study, the researcher used observation techniques, interviews, and document studies to collect data in order to obtain concrete data that accurately reflects what is in the field. From the research findings, the researchers discovered that the factor influencing the selection of the Kubuku Application as the digitalization of the STIKES Buleleng library is the benefits gained from implementing the Kubuku Application in the library. Then, in implementing the Kubuku Application at STIKES Buleleng, the library encountered several obstacles in its application. However, the library staff have thought of ways to overcome those obstacles. In addition, the impact felt during the implementation of the Kubuku Application affects both the teaching lecturers and the students, as well as impacting the literacy program at STIKES Buleleng. Keywords : Library, Kubuku, STIKES, Student